Neutral beam injection for fusion reactors: technological constraints versus functional requirements. (20th September 2021) - Hopf, C.; Starnella, G.; den Harder, N.; Fantz, U.
Abstract: In this paper we look at the technological constraints of neutral beam injection (NBI) systems and compare them with the functional requirements that NBI has in the various envisaged plasma scenarios for tokamak fusion reactors of the DEMO and fusion power plant (FPP) class. We show in particular that there is an intermediate beam energy range in which beamlines are unattractive because of size. Furthermore, for scenarios that consider NBI only for ion heating during the ramp-up and heat-to-burn phase we show that the use of beam energies in the range of 100 to 200 keV, which could be produced from positive ion beams with a much simpler system, could be an attractive option that should be further investigated.